Pengembangan Media Patunglahan untuk Pembelajaran Matematika pada Siswa Kelas I SD Negeri Ketangi - Angger Aulia Artha; Rintis Rizkia Pangestika; Titi Anjarini (STKIP Subang, 2026)
Mathematics instruction in the lower grades of elementary school requires learning media capable of transforming abstract concepts into concrete learning experiences. Preliminary observations at SD Negeri Ketangi revealed that the teaching of addition was dominated by lecture methods and simple visual aids, resulting in low student engagement and limited conceptual understanding. This study aimed to develop the